Effect of La2O3 addition on the synthesis of tungsten nanopowder via combustion-based method. (1st December 2020) - Chen, Zheng; Qin, Mingli; Yang, Junjun; Zhang, Lin; Jia, Baorui; Qu, Xuanhui
Abstract: In this study, the influences of La2 O3 added on the phase, morphology and reduction process of tungsten oxide prepared by solution combustion synthesis (SCS) were investigated for the first time. And tungsten nanopowders with different La2 O3 doping amount (0.5∼5.0 wt%) were successfully prepared by SCS and followed hydrogen reduction. The results showed that with the increase of La2 O3 addition, the product synthesized by SCS changed from needle-like W18 O49 to irregularly granulated H0.53 WO3 and the complete reduction temperature also increased form 700 ℃ to 850 ℃. The densification behavior of as-prepared W nanopowders revealed that the densification inhibitory effect of La2 O3 was enhanced as the La2 O3 addition increased. Nevertheless, due to the optimal size and distribution of La2 O3 particles, the sample with 2.0 wt% La2 O3 addition has a smallest grain size of 0.47 μm and a highest microhardness value of 739.3 Hv0.2, which are the best compared with the literature.